2020
DOI: 10.22161/ijaers.75.41
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Potentially Host Weeds of Planococcus spp. in Coffee Crops

Abstract: Planococcus spp. can cause losses close to 100% of the conilon coffee production in highly infested crops. It is a polyphagous pest that affects several cultures and can be present in host plants that appear spontaneously in the cultivation areas. In this context, the objective was to carry out the survey of weed hosts for mealybug in conilon coffee crops relating to the phenological stage of the culture. For this, the survey was carried out in two areas cultivated with conilon coffee in the northwest region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
(4 reference statements)
1
3
0
Order By: Relevance
“…Fornazier et al (2018), also noted the preference of citrus mealybug for the root system of weeds associated with conilon coffee, proving that this is a place of refuge. Fornaciari et al (2020) found 17 species of host weeds of citrus mealybug in conilon coffee crops, distributed within the botanical families: Asteraceae, Malvaceae, Poaceae, Amaranthaceae, Cyperaceae, Solanaceae, Commelinaceae, Portulacaceae and Cucurbitaceae, demonstrating the potential of weeds as host and source of inoculum for infestations during the flowering and fruiting phase, similar to that observed by Bastos et al (2007) in cotton growing areas with the occurrence of P. minor.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Fornazier et al (2018), also noted the preference of citrus mealybug for the root system of weeds associated with conilon coffee, proving that this is a place of refuge. Fornaciari et al (2020) found 17 species of host weeds of citrus mealybug in conilon coffee crops, distributed within the botanical families: Asteraceae, Malvaceae, Poaceae, Amaranthaceae, Cyperaceae, Solanaceae, Commelinaceae, Portulacaceae and Cucurbitaceae, demonstrating the potential of weeds as host and source of inoculum for infestations during the flowering and fruiting phase, similar to that observed by Bastos et al (2007) in cotton growing areas with the occurrence of P. minor.…”
Section: Discussionsupporting
confidence: 73%
“…The weed sampling process should be carried out, preferably, in the species Bidens pilosa L. and Ageratum conyzoides L. because they are easily found in conilon coffee plantations and for demonstrating greater susceptibility to the occurrence of citrus mealybug (Fornaciari et al, 2020;Fornazier et al, 2019).…”
Section: Phenological Stages Of Conilon Coffee (Varietymentioning
confidence: 99%
“…Here, N=S+I+R is independent of time t and denotes the total population size [8] , [18] , [55] , [56] , [69] . The population of India in 2020 is estimated as 1,380,004,385 people at mid-year according to the UN data [57] .…”
Section: Estimation Of Parameters Of Sir Model Of India Using An Actumentioning
confidence: 99%
“…Here, N=S+I+R, is independent of time t, denotes the total population size [8, 22, 54-56]. India 2020 population is estimated at 1,380,004,385 people at mid-year according to UN data.…”
Section: Introductionmentioning
confidence: 99%